Improving the program performance through prioritized memory management and disk operation. (29th April 2014) - Yeh, Tsozen; Yang, Shuwen; Sun, Yifeng; Limet, Sébastien; Smari, Waleed W.; Spalazzi, Luca; Hu, Jia; Gao, Jianliang
Summary Computers are indispensable to modern human society. Often, computers host multiple programs running simultaneously. However, among those programs, some maybe more time critical than others to users. Consequently, users would hope those time‐critical programs to finish their execution as soon as possible. Generally speaking, the course of program execution includes cooperative operation of CPU, memory, and hard disk. For CPU operation, modern computer systems have the ability to adjust the CPU scheduling sequence according to program priority. Nevertheless, most of them do not have effective ways to provide memory management and disk operation based on program priority. Consequently, it is hard to speed up the execution of prioritized programs as users would expect. The Linux operating system has been widely used in recent years. Even though it still does not support fully‐prioritized memory management and disk operation. Previously, based on the default Linux disk scheduler, complete fair queuing (CFQ), we proposed a new disk scheduling algorithm called prioritized CFQ (PCFQ) to provide fully‐prioritized disk operation. PCFQ had demonstrated good performance improvement for programs with high priority. In this paper, we report our effort to integrate PCFQ with prioritized memory management as a whole in the Linux operating system. With the cooperation between prioritized memory management and prioritized disk operation, our system further enhanced the performance that PCFQ achieved by up to 62.08%. Experimental results also showed that, compared with the current Linux system, our design can lift the performance of individual prioritized programs by up to 76.63% when there was one prioritized program on the system. The number went up to 82.45% when the system hosted three programs with high priority.Concurrency and Computation: Practice and Experience.Copyright © 2014 John Wiley & Sons, Ltd.